Navigating failure : bankruptcy and commercial society in Antebellum America - Balleisen, Edward J. (Luther Hartwell Hodges series on business, society, and the state., 2001)
Examining the shifting character of American capitalism, this volume explores the economic roots and social meanings of bankruptcy, assessing the impact of widespread insolvency on the evolution of American law, business culture and commercial society.